Travel and Transportation Reform Act of 1998 : Implementation. (U.S. Congressional Research., 1999)
Summarizes and analyzes provisions of the Travel and Transportation Reform Act of 1998, which amended policies governing Federal government travel. Reviews changes such as the use of travel charge cards and test programs.